The varying mass distribution of molecular clouds across M83 - Freeman, Pamela; Kruijssen, Diederik (Arxiv, 2017)
The work of Adamo et al. (2015) showed that the mass distributions of young massive stellar clusters were truncated above a maximum-mass scale in the nearby galaxy M83 and that this truncation mass varies with galactocentric radius. Here, we present a cloud-based analysis of ALMA CO($1→ 0$) observations of M83 to search for such a truncation mass in the molecular cloud population. We identify a population of 873 molecular clouds in M83 that is largely similar to those found in the Milky Way and Local Group galaxies, though clouds in the centre of the galaxy show high surface densities and enhanced turbulence, as is common for clouds in high-density nuclear environments. Like the young massive clusters, we find a maximum-mass scale for the molecular clouds that decreases radially in the galaxy. We find the most massive young massive cluster tracks the most massive molecular cloud with the cluster mass being $10^{-2}$ times that of the most massive molecular cloud. Outside the nuclear region of M83 ($R_{g}>0.5$ kpc), there is no evidence for changing internal conditions in the population of molecular clouds, with the average internal pressures, densities, and free-fall times remaining constant for the cloud population over the galaxy. This result is consistent with the bound cluster formation efficiency depending only on the large-scale properties of the ISM, rather than the internal conditions of individual clouds.
Gesehen am 19.10.2017